PSYCHOLOGICAL CHARACTERISTICS OF READING - Ataev Shukur-Ali Ayub-Alievich (Journals Park Publishing, 2023)
This article examines the psychological characteristics of reading in foreign language classes, and also suggests the positive impact of reading on human activity and effective ways to overcome life's difficulties. And also, attention is paid to the psychological characteristics of reading, analysis of its definition and classification in the scientific literature. The positive influence of reading on human activity and ways to overcome life's difficulties is proposed.
Keywords: Foreign Language, The German Language, method, education, psychology, development, types of speech activity, reading.”